Toward an efficient determination of tissue-free water tritium in food - Ren, Hong; Ma, Xiaoxiang; Zhou, Lei; Wang, Peng; Chen, Ting; Zou, Xiao; Zou, Hua; Yu, Shunfei; Cao, Yi; Lai, Zhongjun; Lou, Xiaoming; Cao, Yiyao (Frontiers in Public Health, 2023)
Introduction Tritium in the environment constitutes a radiological concern because it can become part of the hydrogen pool in environmental and biological reservoirs and thereby expose people to radiation. Methods Tissue-free water tritium (TFWT) analysis in food is an important subject of environmental radiation monitoring which plays an important role in the estimation of health risks from environmental tritium exposure. At present, tritium content in food is generally determined by liquid scintillation counter (LSC). To improve the analytical efficiency in tritium determination, we developed a novel method to treat TFWT in food using microporous membranes. Results The microporous membrane treatment method developed in this study has the following characteristics: It has a wide range of application and can process TFWT samples with conductivity below 5 μS/cm. Sample loss for the microporous membrane treatment is approximately 5%. The average treatment time is only 5 min, significantly shortened compared with the currently used atmospheric distillation treatment method (1.5 h). The results of the comparison and spike experiment show that the samples prepared by microporous membrane treatment provides equally satisfactory tritium measurement results as classic distillation method. Discussion The developed microporous membrane method is simple to operate, efficient, and environmentally friendly, and effectively improves the analysis efficiency of TFWT in food.